2021
DOI: 10.1038/s43018-021-00201-z
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan metabolism drives dynamic immunosuppressive myeloid states in IDH-mutant gliomas

Abstract: The dynamics and phenotypes of intratumoral myeloid cells during tumor progression are poorly understood. Here we define myeloid cellular states in gliomas by longitudinal single-cell profiling and demonstrate their strict control by the tumor genotype: in isocitrate dehydrogenase (IDH)-mutant tumors, differentiation of infiltrating myeloid cells is blocked, resulting in an immature phenotype. In late-stage gliomas, monocyte-derived macrophages drive tolerogenic alignment of the microenvironment, thus preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
140
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 63 publications
3
140
0
Order By: Relevance
“…So far, many CNS pathologies and their respective animal models have been analyzed using single-cell RNA sequencing approaches, e.g. Alzheimer's disease [27,48], Multiple Sclerosis [26,36] or gliomas [12]. Intracerebral macrophages other than microglia, i.e.…”
Section: Assessing Microglia Heterogeneity On the Single-cell Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many CNS pathologies and their respective animal models have been analyzed using single-cell RNA sequencing approaches, e.g. Alzheimer's disease [27,48], Multiple Sclerosis [26,36] or gliomas [12]. Intracerebral macrophages other than microglia, i.e.…”
Section: Assessing Microglia Heterogeneity On the Single-cell Levelmentioning
confidence: 99%
“…Single-cell technologies have tremendously helped to better understand CAMs/BAMs in health and disease [26,43,73]. Single-cell RNA-sequencing was able to define myeloid cell clusters in isocitrate dehydrogenase (IDH) 1 mutant astrocytomas that were not present in IDH-1 wild-type gliomas, which may have both diagnostic and therapeutic consequences [12].…”
Section: Assessing Microglia Heterogeneity On the Single-cell Levelmentioning
confidence: 99%
“…As such, a clearer understanding of different effects of R-2-HG in the TME is expected to yield better therapy opportunities. In a new study in Nature Cancer, Friedrich et al provide new insights into how R-2-HG elicits suppressive gliomaassociated macrophages (GAMs), opening up new avenues for intervention [5].…”
mentioning
confidence: 99%
“…Friedrich and colleagues explored the different immune cell populations present in the TME of human gliomas [5]. Using single-cell RNA-sequencing and mass cytometry, they demonstrated that myeloid cells from patients with IDH-mutant gliomas showed lower expression of antigen presentation-associated proteins, suggesting a more immunosuppressive phenotype in comparison with IDH-WT GAMs.…”
mentioning
confidence: 99%
See 1 more Smart Citation